Lymphangioma Circumscriptum – A Rare Cause of Gingival Enlargement: A Case Report and Review of Literature - Sadasivan A; Ramesh R (Dove Medical Press, 2022)
Arun Sadasivan,1 Roshni Ramesh2 1Department of Periodontics, SMIDS, Kulashekaram, Tamil Nadu, India; 2Department of Periodontics, Government Dental College, Trivandrum, Kerala, IndiaCorrespondence: Arun Sadasivan, Department of Periodontics, SMIDS, Kulashekaram, Tamil Nadu, India, Tel +91 9847246961, Email sadasivan_arun@hotmail.comBackground: Lymphangiomas or microcystic lymphatic malformations (MLM) are hamartomatous formations that occur due to the proliferation of lymphatic vessels. They commonly manifest in the head and neck region with only a few cases reported within the oral cavity. Lymphangioma circumscriptum in the gingiva is a rare condition which presents as asymptomatic pebbly gingival enlargement. They are characterized by lesions that are microscopic thin-walled cysts. Histopathologically, they show multiple dilated lymphatic channels which are lined by endothelial cells. The lumen is filled with lymphatic fluid, red blood cells, and other inflammatory cells. These are dispersed within connective tissue stroma. Multiple modalities of treatment have been reported, including surgical excision, laser therapy, and sclerotherapy.Case Presentation: This paper reports a rare case of multiple lymphangiomas of the gingiva in a 21-year-old female patient. The clinical picture, surgical treatment, histologic features, and immunohistochemistry [IHC] findings are presented. The histologic findings of lymphangioma were confirmed with IHC being positive for lymphatic marker D2-40. The patient was followed up for a period of 2 years, with no recurrence noted.Conclusion: Lymphangiomas or microcystic lymphatic malformations presenting as a gingival enlargement are a rare occurrence. Therefore, lymphangiomas may also be considered in the differential diagnosis of gingival enlargements.Keywords: gingiva, gingival enlargement, immunohistochemistry, lymphangioma, maxilla, oral